‘The Claims about Religion Dying Out are a Terminological Self-delusion’: Emanuel Chalupný’s Contribution to Czech Sociology of Religion - Nešpor, Zdeněk R.; Knotková , Veronika (Dějiny – teorie – kritika, 2009)
This article describes the life and work of an important Czech sociologist of the interwar period, Emanuel Chalupný (1879–1958). Even from a mere outline of his life one clearly sees that he was a highly controversial, tenacious, even disagreeable figure, who had no intention of giving in to anyone or anything, something that earned him many enemies. His own extraordinarily numerous works of sociology are today outmoded, yet they contain a number of original ideas, which contemporaneous critics often overlooked. One of the areas where Chalupný made interesting contributions is the sociology of religion, which developed in an original way the ideas of Auguste Comte and follows on Tomáš Garrigue Masaryk. Chalupný appreciated both individual mysticism and the thorough church organization, and was able to perceive the religious dimensions of works of art, particularly literary ones, as well as political forms of ‘implicit religions’. His own attitude to religion, however, stemmed from his religious feeling, at least to a certain extent, which had developed in the context of the religious and non-religious opinions of contemporaneous Czech intellectuals (though not always in agreement with them). This dimension of Chalupný’s personality is examined in the article, wherever the sources have permitted, as well as the unfortunate conclusion of his life after the Communist takeover in Czechoslovakia.